Effect of multidisciplinary nursing intervention on interdialytic weight gain and quality of life among chronic hemodialysis patients: A randomized controlled trial - Rashmimala Pradhan; Pravati Tripathy; Debaprasad Kar (Journal of Integrative Nursing)
Objectives: This study was conducted to determine the effect of multidisciplinary nursing intervention (MNI) on interdialytic weight gain (IDWG) and quality of life (QoL) among chronic hemodialysis patients. Materials and Methods: Quantitative research approach with randomized-controlled, single-blind trial was conducted among 120 chronic hemodialysis patients in Institute of Medical Sciences and SUM Hospital Bhubaneswar, Odisha, India from February 2023 to February 2024. Participants were randomly assigned into the experimental group (n1 = 65) and control group (n2 = 55) by block randomization methods. The experimental group received the intervention phase up to the 6th week, along with the usual treatment, and the control group received only standard treatment up to the end of the study. After that, they received the diet chart plan and fluid distribution timetable. Results: Significant improvements were found in IDWG and QoL for the experimental group. The experimental group exhibited a sharp decline in weight gain within the group (F = 20.05, P < 0.001) between the group (F = 13.02, P < 0.001), interaction effects between the groups across the time point (F = 5.67, P < 0.005). Kidney disease QoL scores (KDQOL™ 36) increased from 49.38 ± 9.56 to 58.63 ± 6.04 in the experimental group, compared to an increase from 50.84 ± 9.25 to 52.04 ± 8.02 in the control group. Conclusion: This trial showed that MNIs significantly reduced IDWG and improved KDQOL™ 36 scores, with the experimental group outperforming the control, highlighting the intervention’s effectiveness.